2013
DOI: 10.5935/abc.20130099
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Assessment by Tissue-Doppler Echocardiography in Acute Pulmonary Embolism

Abstract: In PTE, RV dysfunction on echocardiography is accompanied by BNP elevation; although tissue-Doppler imaging adequately confirms the presence of RV dysfunction, it has a limited sensitivity for this diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
1
14
2
Order By: Relevance
“…In previous studies, increased BNP levels were demonstrated to be associated with adverse outcomes and RVD in patients with APE [26][27]. Ohigashi et al [26] investigated the role of BNP, D-dimer, troponin I, and C-reactive protein in predicting adverse outcomes and RVD in patients with APE and they demonstrated that only high plasma BNP level was found to be a predictor of RVD and short-and long-term prognosis of APE.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, increased BNP levels were demonstrated to be associated with adverse outcomes and RVD in patients with APE [26][27]. Ohigashi et al [26] investigated the role of BNP, D-dimer, troponin I, and C-reactive protein in predicting adverse outcomes and RVD in patients with APE and they demonstrated that only high plasma BNP level was found to be a predictor of RVD and short-and long-term prognosis of APE.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tissue Doppler variables, both tissue Doppler s' velocities, an estimate of RV longitudinal function, and RV MPI, an index that incorporates systolic and diastolic function, correlated weakly to the severity of vascular obstruction. Despite the extensive data using tissue Doppler velocities for RV assessment [14,15], this analysis can be influenced by age, loading conditions and the presence of significant tricuspid regurgitation [16]. In a few patients with large PE and RV dysfunction (demonstrated both qualitatively and by FAC), RV myocardial s' velocities were not decreased if significant tricuspid regurgitation was present.…”
Section: Discussionmentioning
confidence: 98%
“…We would like to thank Yalcinkaya et al 1 and coworkers for the worthy commentaries on our recent article 1 . Brain natriuretic peptide (BNP) is produced primarily in ventricular myocytes, and elevated levels are found mainly in patients with increased left ventricular and pulmonary artery pressure.…”
mentioning
confidence: 91%
“…We read with great interest the article by Rodrigues et al 1 entitled "Right Ventricular Assessment by Tissue-Doppler Echocardiography in Acute Pulmonary Embolism", which was published of the Arquivos Brasileiros de Cardiologia. The authors 1 aimed to evaluate the right ventricular (RV) systolic function using two-dimensional tissue Doppler echocardiography in patients with acute pulmonary embolism (PE) and to analyze its correlation with atrial natriuretic peptide (BNP) levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation